(untitled) (Namibian Journal for Research, Science and Technology, 2020)
Lithium is a unique metal and a raw material for the batteries of electronic equipment and electric cars, making it one of the most valuable elements in the Industry 4.0 era. The Karibib Pegmatite Belt (KPB) has been prospected for lithium mineralization since the 19th century. There is however a need for detailed studies of lithium-bearing pegmatites in this area. This research therefore focuses on the distribution and occurrence of lithium-bearing minerals within the Helikon pegmatites (5 and 6), and develops a criterion that can be used for lithium exploration. The Helikon pegmatites are some of the pegmatites that occurs within the KPB. Both Helikon 5 and 6 pegmatites show well developed zonation, with discrete and discontinuous mineralization restricted to areas with well-developed internal zonation. The primary lithium mineralization is characterized by purple and grey lepidolite, with minor amounts of petalite. Furthermore, lithium mineralization occurs as both massive and disseminated at the Helikon 5 and 6 pegmatites, but it also occurs as banded at Helikon 6. ICP-MS analysis determined an overall lithium grade of 3.01%_Li2O and XRD was used to identify all the lithium bearing minerals. The provenance of the Helikon 5 and 6 pegmatites is found to be from Damaran S-type granites. The fractionation coefficients showed that Helikon 5 and 6 pegmatites are both highly fractionated pegmatites, but Helikon 5 is more prospected for lithium mineralization than the Helikon 6 pegmatite.